PEMASARAN ONLINE SEBAGAI SARANA PROMOSI PRODUK RAJUTAN DI KECAMATAN RUMBAI PEKANBARU - Wahyuningsih, Endah (Jurnal Daya Saing, 2024)
This research is a type of experimental research. The data collection method used observation techniques on mothers in Rumbai District, Pekanbaru City. Observations were carried out on 18 respondents by filling in a research questionnaire in a Google form. Online marketing has not been optimally utilized in promoting knitted products, even though 50% of respondents use Instagram and 61% of Facebook, the age factor is very influential, 78% are over 50 years old so mothers are not yet familiar with using social media for business needs. Follow-up training is needed in the form of knitting training, graphic design, internet, web creation and processing, as well as trademark creation training for knitters to be more enthusiastic, increase sales, develop well and become an alternative family income. Keywords :